The influence of baseline characteristics on the efficacy of immune checkpoint inhibitors for advanced lung cancer: A systematic review and meta-analysis - Xiao, Qionghua; Yu, Xiaolin; Shuai, Zhihao; Yao, Ting; Yang, Xiaohua; Zhang, Yanxia (Frontiers in Pharmacology, 2022)
Purpose: To investigate the impact of different baseline characteristics on the efficacy of immune checkpoint inhibitors (ICIs) for advanced lung cancer. Methods: In order to identify eligible randomized controlled trials (RCTs), a systematic search was conducted in PubMed, EMBASE, and Cochrane library databases. The primary outcomes were hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS). To explore the potential interaction during the administration of ICI, patients were stratified by baseline characteristics. Results: The meta-analysis included 24 RCTs. ①Compared with non-ICI therapy, patients with lung cancer benefitted more from immunotherapy (HR, 0.78; P < 0.0001). ②Patients without liver metastases could get more survival benefits than those with liver metastases (HR, 1.20; P = 0.0139). Similar outcomes were also observed in following subgroups: small cell lung cancer (HR, 1.20; P = 0.0433), subsequent line (HR, 1.40; P = 0.0147), and ICI monotherapy (HR, 1.40; P = 0.0147). ③Subgroup analysis showed that tumor type affected the efficacy of immunotherapy in patients with brain metastases (HR, 0.72 vs 1.41; interaction, P < 0.01). Among patients with smoking history (HR, 0.87 vs 1.23; interaction, P = 0.05) and brain metastases (HR, 0.69 vs 1.21; interaction, P = 0.05), the type of therapy (i.e., monotherapy or combination therapy) had potential influences on the efficacy of immunotherapy. Conclusions: Some critical baseline characteristics could indicate the efficacy of ICI therapy. Liver metastasis status could predict the efficacy of ICI therapy for lung cancer. Compared with small cell lung cancer, patients with brain metastases might have more durable OS in non-small cell lung cancer. The smoking history or brain metastasis status of patients could indicate the potential clinical benefits of monotherapy or combination therapy.